Identifikasi Perilaku Perundungan Verbal Terhadap Motivasi Belajar Siswa Kelas V SD Inpres Antang I Kota Makassar - Efruan, Ratu Juliana; Muh. Khaedar; Baharuddin Hafid; Jusmawati (Mataram University, 2024)
The aim of the research is to find out what the factors that causes of bullying behaviour on student motivation in class V SD Inpres Antang I Makassar. This study used descriptive method with a qualitative approach. Subjects of study are students class V SD Inpres Antang I Makassar. The data collection technique used was observation, in-depth interviews, and documentation. Results show that there were several factors that cause the occurrence verbal bullying behaviour in class V , including: because they were often bullied by their classmates, the emotions that excessive, quiet children, association, social media and attention from parents. As the impact of verbal bullying that occurred in class V is negative towards student learning motivation of class V SD Inpres Antang I Makassar for causing students did want to go to school, lazy to study because they always think of harsh words that raised by their classmates, not confident and some even scared to hang out with classmates.